GAMBARAN TINGKAT KECEMASAN PADA PASIEN STROKE DI RUANG BELIBIS RSUD WANGAYA DENPASAR - Dewa Ketut Saputra; Ni Made Sri Muryani; I Made Sukarja; Ni Made Wina Krisnayani (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2018)
Background: Stroke is a major cause of disability in adults, where four million Americans experience neurological deficits due to stroke, two-thirds of these deficits are moderate to severe. This disease has become a worldwide health problem and is increasingly important, with two-thirds of strokes now occurring in developing countries. Stroke sufferers themselves will experience a psychological response, namely anxiety because in addition to being a life threat, patients will feel anxious about their future. The purpose of this study was to determine the description of the level of anxiety in stroke patients in the Belibis Room of Wangaya Hospital Denpasar. Methode: The type of design used is descriptive design. Data collection was carried out by the researchers themselves using a standard questionnaire sheet, the Hamilton Anxiety Rating Scale (HARS), with the number of respondents 30 people who were Stroke patients in the Belibis room of Wangaya Hospital Denpasar. Result: The results of this study indicate that the majority of stroke patients in the Belibis room of Wangaya Hospital Denpasar experienced moderate anxiety, namely as many as 17 (56.7%) respondents, mild anxiety as many as 6 (20%) respondents, severe anxiety as many as 6 (20%) respondents, panic 0%, and only 1 (3.3%) respondents who did not experience anxiety. Conclusion: Individuals who experience anxiety are mostly aged over 50 years, female sex, high school education, and have private jobs. It is expected that families can provide motivation and positive encouragement to patients.Keywords: Anxiety Level; Stroke Patients